Malay Islamic Leadership as a Model of Moral and Spirituali-ty-Based Leadership in the Modern Era (Lembaga Pengembangan Kinerja Dosen, 2025)
This study is motivated by the moral and spiritual crisis affecting modern leadership systems, where the exercise of power often prioritizes material and political interests over ethical values and social responsibility. In this context, the concept of Malay Islamic Leadership is considered relevant as an alternative model that integrates moral, spiritual, and local cultural values to establish a just and civilized governance framework. The purpose of this study is to describe the fundamental principles of Malay Islamic leadership, analyze the implementation of its moral and spiritual values, and assess its relevance in addressing the challenges of modern leadership. The research employed a qualitative descriptive method using secondary data obtained through literature reviews of books, journal articles, and academic documents discussing Islamic leadership and Malay culture. The results indicate that Malay Islamic leadership is founded on the values of amanah (trustworthiness), ‘adl (justice), hikmah (wisdom), and syura (consultation), while taqwa (piety) serves as the core of a leader’s spirituality. These values are proven to be relevant in the modern context as they address ethical crises, strengthen leaders’ integrity, and reorient leadership toward service and the welfare of the community.